2015
DOI: 10.1021/acs.est.5b00060
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas and Cellulosic Biomass: A Clean Fuel Combination? Determining the Natural Gas Blending Wall in Biofuel Production

Abstract: Natural gas has the potential to increase the biofuel production output by combining gas- and biomass-to-liquids (GBTL) processes followed by naphtha and diesel fuel synthesis via Fischer-Tropsch (FT). This study reflects on the use of commercial-ready configurations of GBTL technologies and the environmental impact of enhancing biofuels with natural gas. The autothermal and steam-methane reforming processes for natural gas conversion and the gasification of biomass for FT fuel synthesis are modeled to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…40 Wright et al investigated the NG blending wall in biofuel production. 41 In this study, they showed that less than 19.1% of NG on an LHV energy basis (7.83 wt%) could be blended to avoid exceeding the emissions limits established by the Renewable Fuel Standard (RFS) 2. 41 This GBtL TEA provides baseline cost results for hydrocarbon liquid fuel production, which can be viewed as a near-term deployment opportunity for renewable jet fuel production.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…40 Wright et al investigated the NG blending wall in biofuel production. 41 In this study, they showed that less than 19.1% of NG on an LHV energy basis (7.83 wt%) could be blended to avoid exceeding the emissions limits established by the Renewable Fuel Standard (RFS) 2. 41 This GBtL TEA provides baseline cost results for hydrocarbon liquid fuel production, which can be viewed as a near-term deployment opportunity for renewable jet fuel production.…”
Section: Introductionmentioning
confidence: 84%
“…41 In this study, they showed that less than 19.1% of NG on an LHV energy basis (7.83 wt%) could be blended to avoid exceeding the emissions limits established by the Renewable Fuel Standard (RFS) 2. 41 This GBtL TEA provides baseline cost results for hydrocarbon liquid fuel production, which can be viewed as a near-term deployment opportunity for renewable jet fuel production. Sensitivity analyses are performed to identify key cost drivers and guide future R&D, as well as near-term deployment strategies.…”
Section: Introductionmentioning
confidence: 84%
“…A far more reaching challenge arises to introduce advanced polymers as hot-melt adhesives, to provide a combination of sustanable origin, technological effectiveness, and reusability. Indeed, this is the area where the advantages of biomass-derived renewable materials should be explored. …”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analyses are performed to identify the impacts of FT kinetics on overall production costs. Limited studies focus on TEA for natural gas and biomass to liquid (GBtL) . Chakravarti et al .…”
Section: Introductionmentioning
confidence: 99%
“…employed an optimization‐based framework to perform a technoeconomic and environmental assessment of a GBtL process, and the effect of including carbon capture and sequestration in a GBtL process was analyzed by Liu et al . The percentage of natural gas in establishing a blending wall for the GBTL process was investigated by Wright et al ., and it was determined that the use of natural gas should be limited to less than 19.1% on a LHV energy basis (7.83 wt%) to avoid exceeding the emission limits established by the Renewable Fuels Standard (RFS2) for clean, advanced biofuels . In this study, we model the steam‐reforming process for NG conversion and the indirect gasification of biomass for FT fuel synthesis to provide a better understanding of the processes.…”
Section: Introductionmentioning
confidence: 99%